SINKRONISASI PERATURAN PRESIDEN DENGAN PERATURAN DAERAH TENTANG IZIN USAHA MIKRO KECIL (UMK) DAN IMPLIKASINYA DI KABUPATEN GUNUNG MAS - Dwi Saputra Yulianus (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2018)
This research resulted in the followings. First, the implementation of the Presidential Decree No. 98 year of of 2014 concerning Licensing of Micro Small Businesses with the Local Regulation of Gunung Mas regency No. 6 year of 2011 is contradictory, since the making of micro business licenses in Gunung Mas regenc is put together with the advertisement tax, and the advertisement tax is used as one of the conditions for the issuance of a micro business permit. This is what makes the Presidential Decree contradictory with the Local regulation. Second, in the field, many business people are confused with the Presidential Decree due to the lack of socialization carried out by the government, whereas the issuance of the Presidential decree is intended to increase business actors and to facilitate the process of making micro-business licenses. Key Words: Synchronization, Implementation, Licensing, Advertising Taxes